2021
DOI: 10.32615/ps.2021.061
|View full text |Cite
|
Sign up to set email alerts
|

The melatonin receptor CAND2 is involved in the regulation of photosynthesis and chloroplast gene expression in Arabidopsis thaliana under photooxidative stress

Abstract: Abbreviations: Fv/Fm -maximum quantum yield of PSII; HL -high light; MS -Murashige and Skoog medium; NEP -single-subunit nuclear-encoded RNA polymerase of the phage-type; NPQ -nonphotochemical quenching; PAM -pulse amplitude modulation; PEP -bacterial type plastid-encoded RNA polymerase; RT-qPCR -quantitative Real-Time PCR; WT -wild type; ФPSII -effective quantum yield of PSII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It has been shown that melatonin can protect photosystem and enhance photosynthetic capacity in vascular plants exposed to different environmental stresses ( Yin et al, 2013 ). Recent studies showed that melatonin improved photosynthetic efficiency probably through regulating the CAND2/PMTR1-mediated signaling pathway ( Bychkov et al, 2021 ; Yang et al, 2022 ), reducing chlorophyll degradation, and alleviating the damage to the integrity of thylakoid membrane via increasing the expression levels of electron-transport-related proteins under NO 2 stress ( Wang et al, 2022 ). In this study, exogenous melatonin application at 25 μM effectively improved the photosynthetic capacity of PSII under osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that melatonin can protect photosystem and enhance photosynthetic capacity in vascular plants exposed to different environmental stresses ( Yin et al, 2013 ). Recent studies showed that melatonin improved photosynthetic efficiency probably through regulating the CAND2/PMTR1-mediated signaling pathway ( Bychkov et al, 2021 ; Yang et al, 2022 ), reducing chlorophyll degradation, and alleviating the damage to the integrity of thylakoid membrane via increasing the expression levels of electron-transport-related proteins under NO 2 stress ( Wang et al, 2022 ). In this study, exogenous melatonin application at 25 μM effectively improved the photosynthetic capacity of PSII under osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…CAND2 could regulate photooxidative stress by inducing the expression of chloroplast (ELIP1) and nuclear gene (LHCB2). 271 GmWRKY16 overexpressing significantly increased plant drought resistance by mediating the expression of stressrelated genes such as RD29A, RD22, KIN1, and LEA14. 272 Consistent with this, GmNAC11 and CarNAC4 from soybean and chickpea regulated DREB1A, ERD11/10, COR15A/47, RD29A, ERF5, RAB18, KIN1 and KAT2 to build drought and salt tolerance.…”
Section: Abiotic Stressmentioning
confidence: 95%
“…The high expression of resistance‐associated genes is an important mechanism for melatonin to improve abiotic stress tolerance (Figure 7A). CAND2 could regulate photooxidative stress by inducing the expression of chloroplast ( ELIP1 ) and nuclear gene ( LHCB2 ) 271 . GmWRKY16 overexpressing significantly increased plant drought resistance by mediating the expression of stress‐related genes such as RD29A , RD22 , KIN1 , and LEA14 272 .…”
Section: Melatonin Signal Transductionmentioning
confidence: 99%
“…In that case, the melatonin-dependent alleviation of plant growth restriction, the total amount of ROS following osmotic stress, and the expression level of several ROS processing enzymes following the stress were all AtPMTR1-dependent. Similarly, some evidence for an AtPMTR1 dependency for the melatonin alleviation of high-light stress in Arabidopsis also exists ( Bychkov et al, 2021 ). Moreover, the involvement of PMTR1 in the melatonin-induced response is not restricted to Arabidopsis .…”
Section: Melatoninmentioning
confidence: 99%